Évolution des principales communautés benthiques du secteur marin situé devant les embouchures du Danube pendant la période 1977 -1980 - Țigănuș, Victoria (Cercetări Marine - Recherches Marines, 2026)
Qualitative and quantitative changes in benthic communities situated close to the Danube mouths are discussed. Comparative with previous references there is a general simplification concerning structure and reduction of densities within communities such as Corbula sands transitory to muds with Spisula, the muds with Corbula-Syndesmia-Cardimm association, and the muds with Mytilus.